2009
DOI: 10.1111/j.1365-2265.2009.03615.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of PPARγ allelic variation, osteoprotegerin and abdominal aortic aneurysm

Abstract: Objective-We have previously demonstrated high concentrations of the glycoprotein osteoprotegerin (OPG) in biopsies of abdominal aortic aneurysm (AAA) and demonstrated that ligation of the nuclear receptor peroxisome proliferator-activated receptor gamma (PPARγ) downregulates OPG in vitro and within a mouse model. The aims of this study were to assess the associations between circulating concentrations of OPG, polymorphisms of the gene encoding PPARγ (PPARG), AAA presence and growth.Design, patients and measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 31 publications
2
30
0
2
Order By: Relevance
“…[18][19][20][21] Circulating OPG concentrations have also been reported to be higher in patients with AAA and positively associated with AAA progression. 4,22 In vitro experiments have suggested that OPG stimulates matrix metalloprotease (MMP) secretion from human monocytes and VSMCs, and that OPG secretion is downregulated by irbesartan. 4 These data suggest a potential role of OPG in AAA; however, currently we are aware of no studies that have reported the concentration of OPG in human AAA biopsies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21] Circulating OPG concentrations have also been reported to be higher in patients with AAA and positively associated with AAA progression. 4,22 In vitro experiments have suggested that OPG stimulates matrix metalloprotease (MMP) secretion from human monocytes and VSMCs, and that OPG secretion is downregulated by irbesartan. 4 These data suggest a potential role of OPG in AAA; however, currently we are aware of no studies that have reported the concentration of OPG in human AAA biopsies.…”
mentioning
confidence: 99%
“…Sections were 19 stained for elastin using the elastin von Giesson method, for collagen using Picro-sirius red, 20 and for VSMCs (α-smooth muscle actin), macrophages (CD68), T-lymphocytes (CD3), B-21 lymphocytes (CD20) and plasma cells (CD138) using immunohistochemistry, as previously 22 described. 3 Immunostaining of sections with OPG was performed using the following Intraluminal thrombus measurements 16 All CTA scans were acquired on a 16-or 256-slice CT-scanner (Philips Medical Systems,…”
mentioning
confidence: 99%
“…We next created a Galbraith plot to graphically assess the source of the heterogeneity. As a result, five studies 15,28,32,34,37) were identified as the main contributors of heterogeneity for the allelic models, two studies 15,37) were identified as the main contributors of heterogeneity for the additive and recessive models and four studies 11,28,32,37) were identified as contributors of heterogeneity for the dominant model (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…Among the included studies, four studies reported that the T allele protects against the risk of CAD 11,22,34,37) : one study showed that the frequency of the TT genotype is significantly higher among patients with acute myocardial infarction than in controls 15) and one study demonstrated that the TT genotype is associated with increased abdominal aortic aneurysm growth 32) . The current study provided no evidence of a significant association between the rs3856806 polymorphism and atherosclerotic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation